Predictors of Success in Digital Oratory: Assessing the Impact of an English Digital Oratory Course on Public Speaking Competence - Diana POPA; Carmen Mihaela CRETU (Revista de Știinţe Educaţiei)
This study sets out to examine the predictors of success in Public Speaking (PS) within digital contexts, referred to as digital oratory (DO), by evaluating the impact of an English Digital Oratory (EDO) course on high school students’ PS competence. Specifically, it investigates how English as a Foreign Language (EFL) proficiency, prior PS experience, and intelligence is associated with PS performance in DO. DO encompasses traditional PS skills while integrating competencies required for virtual engagement and the effective use of digital tools. The study involved a quasi-experimental design, with pre- and post-tests, and a sample of 100 Romanian EFL high school students who attended a six-month EDO course on Google Classroom. Relevant theories, such as educational, EFL, emotional and psychological development, talent and giftedness, and multimedia integration informed our curriculum, framed in Fink’s Taxonomy of Significant Learning. The intervention featured synchronous sessions, peer evaluations, flipped classroom methodology, digital technologies, and interactive and learner-centered activities. We measured PS performance before and after the course using Schreiber’s (2012) Public Speaking Competence Rubric and our results demonstrated a significant improvement in both expert-evaluated and self-reported PS competence. Intelligence primarily is associated with content-related skills, whereas EFL proficiency and prior PS experience had an impact on overall PS competence. Our findings substantiate the fact that EDO instruction should be an integral part of communication education. The research offers valuable insights into replicable efficient digital oratory instruction in EFL, suitable for students with diverse linguistic and cognitive features.